2016
DOI: 10.1111/pan.13003
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream capnography system for nonintubated children in the postanesthesia care unit: Performance with changing flow rates, and a comparison to side stream capnography

Abstract: A new mainstream mask system (cap-ONE) performed with greater precision than side stream NC monitoring regardless of mouth breathing. Measurement of peak CO values by mainstream mask system showed normal distribution with smaller standard deviation (sd) and was less affected by O flow change in predictable fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Two studies demonstrated the Masimo RRa product showed greater sensitivity and specificity than thoracic impedance pneumography or capnography by nasal cannula at detecting apneic events [16,17]. The Infant and Pediatric cap-ONE utilizes a mask with mainstream capnography (Nihon Kohden Corporation, Tokyo, Japan) and more accurately monitors carbon dioxide levels in patients without advanced airways when compared to capnography via nasal cannula [18].…”
Section: Monitoring and Equipmentmentioning
confidence: 99%
“…Two studies demonstrated the Masimo RRa product showed greater sensitivity and specificity than thoracic impedance pneumography or capnography by nasal cannula at detecting apneic events [16,17]. The Infant and Pediatric cap-ONE utilizes a mask with mainstream capnography (Nihon Kohden Corporation, Tokyo, Japan) and more accurately monitors carbon dioxide levels in patients without advanced airways when compared to capnography via nasal cannula [18].…”
Section: Monitoring and Equipmentmentioning
confidence: 99%
“…40 New devices are under development and are being tested for use with a facemask or mouthpiece in children and infants. [41][42][43]…”
Section: Mainstream Capnometry and Capnographymentioning
confidence: 99%